2019
DOI: 10.1186/s13099-019-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of internalin genes in Listeria monocytogenes from food and humans, and their association with the invasion of Caco-2 cells

Abstract: Background Internalins are surface proteins that are utilized by Listeria monocytogenes to facilitate its invasion into human intestinal epithelial cells. The expression of a full-length InlA is one of essential virulence factors for L. monocytogenes to cross the intestinal barrier in order to invade epithelial cells. Results In this study, the gene sequences of inlA in 120 L. monocytogenes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 60 publications
(103 reference statements)
7
24
0
Order By: Relevance
“…This evidence, in the light of experimental evidences collected previously, pointed out that a strong InlA-Ecad interaction might not be essential to determine the cell invasion capacity of L. monocytogenes. Therefore, our results are in line with the finding that InlA has an important, though not exclusive, role in determining the virulence of L. monocytogenes strains, as previously suggested Notably, the sequence of InlA13 investigated in the present work was encoded in a series of L. monocytogenes isolates (e.g., GeneBank accession codes APID00000000 and AWWR00000000) previously assessed for their capability to invade cells [14]. In particular, they showed a mean cell invasion capacity either nearly 1 log CFU higher (as in the case of strain LM438, AWWR00000000) or lower (as in the case of strain SHL004, APID00000000) than the reference EGD-e strain (holding the wt InlA sequence analyzed in the present work).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This evidence, in the light of experimental evidences collected previously, pointed out that a strong InlA-Ecad interaction might not be essential to determine the cell invasion capacity of L. monocytogenes. Therefore, our results are in line with the finding that InlA has an important, though not exclusive, role in determining the virulence of L. monocytogenes strains, as previously suggested Notably, the sequence of InlA13 investigated in the present work was encoded in a series of L. monocytogenes isolates (e.g., GeneBank accession codes APID00000000 and AWWR00000000) previously assessed for their capability to invade cells [14]. In particular, they showed a mean cell invasion capacity either nearly 1 log CFU higher (as in the case of strain LM438, AWWR00000000) or lower (as in the case of strain SHL004, APID00000000) than the reference EGD-e strain (holding the wt InlA sequence analyzed in the present work).…”
Section: Resultssupporting
confidence: 92%
“…In particular, they showed a mean cell invasion capacity either nearly 1 log CFU higher (as in the case of strain LM438, AWWR00000000) or lower (as in the case of strain SHL004, APID00000000) than the reference EGD-e strain (holding the wt InlA sequence analyzed in the present work). On the one hand, our results may provide a mechanistic and InlA-dependent rationale explaining the reduced invasion capacity observed for the strain SHL004 (APID00000000), though they failed to explain those strains with a raised invasiveness [14]. On the other hand, our results pointed out that the strength of InlA-Ecad interaction may not directly relate to the cell invasion capacity reflecting at the same time the possible non-exclusive role of InlA in determining the virulence of L. monocytogenes, in agreement with previous studies [14,17].…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Primarily, this interaction allows L. monocytogenes, where E-cadherin is exposed, to pass through the intestinal epithelial barrier via transcytosis either on the luminal surface around intestinal goblet cells or intercellular junctions that form as part of normal gut homeostasis (Pentecost et al, 2006;Nikitas et al, 2011). It has been demonstrated that heterologous expression of InlA confers the capacity for internalization to the invasion-deficient Listeria innocua, and that natural premature stop codons in the inlA gene of L. monocytogenes clinical isolates are associated with a reduced capacity to invade intestinal epithelium and an increased infective dose in experimental models (Gaillard et al, 1991;Van Stelten et al, 2011;Su et al, 2019).…”
Section: Internalin a Of Listeria Monocytogenesmentioning
confidence: 99%